A Double-Edged Sword? Legal Certainty and the Perils of Authority in Indonesia’s Draft Asset Deprivation Act - Hisbul Luthfi Ashsyarofi; Arfan Kaimuddin; R.B. Muhammad Zainal Abidin; Bastomi, Ahmad (Pandecta Research Law Journal, 2024)
The urgency of enacting the Draft Asset Deprivation Act in Indonesia stems from the need to recover assets linked to criminal activities, even in the absence of a conviction. This approach is seen as a preventive measure to safeguard illicitly acquired assets; however, its implementation raises serious legal concerns. The potential violation of property rights—recognized as fundamental human rights—poses risks to justice and legal certainty. The lack of clear procedural safeguards could lead to authority abuse, arbitrary asset seizures, and disproportionate impacts on individuals. This study identifies critical inconsistencies within the draft law. First, the phrase "asset deprivation is only carried out once" in the explanation of Article 3 contradicts Article 5(1)(c), which allows additional asset deprivation if previously seized assets are insufficient. This antinomy undermines legal certainty and fairness. Second, Article 56 permits the auctioning of assets before a final court decision without specifying clear conditions for its application. The absence of rigid legal criteria opens avenues for abuse of authority, further exacerbating risks of injustice. The novelty of this research lies in its critical legal analysis of these contradictions and their implications for property rights and procedural fairness. This research contributes to the global discourse on asset deprivation laws by critically examining the tension between crime prevention and fundamental human rights. The study highlights how ambiguities in legal drafting and the absence of clear procedural safeguards can lead to authority abuse, a challenge faced by many jurisdictions implementing non-conviction-based asset forfeiture (NCB) frameworks. By comparing Indonesia’s Draft Asset Deprivation Act with international best practices, this research offers valuable insights into the legal balance between state power and individual rights, which is crucial in developing laws that do not unduly compromise fundamental freedoms.